2020
DOI: 10.1186/s13046-020-01719-3
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide inhibits melanoma in vitro and in vivo

Abstract: Background Even though new therapies are available against melanoma, novel approaches are needed to overcome resistance and high-toxicity issues. In the present study the anti-melanoma activity of Nicotinamide (NAM), the amide form of Niacin, was assessed in vitro and in vivo. Methods Human (A375, SK-MEL-28) and mouse (B16-F10) melanoma cell lines were used for in vitro investigations. Viability, cell-death, cell-cycle distribution, apoptosis, Nicotinamide Adenine Dinucleotide+ (NAD+), Adenosine Triphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 85 publications
(108 reference statements)
1
42
0
Order By: Relevance
“…Infiltration of T lymphocytes in the tumor was also increased, thus indicating that Nam was able to activate the anti-tumor T cell response (31). Similar results have been obtained in a mouse model of melanoma (19), where Nam administered alone as a therapeutic agent reduced tumor growth and prolonged the survival of mice. Higher levels of IFN-g-producing cells were found in the peripheral blood of mice treated with Nam than in untreated mice.…”
Section: The Direct Role Of Nad +supporting
confidence: 74%
See 2 more Smart Citations
“…Infiltration of T lymphocytes in the tumor was also increased, thus indicating that Nam was able to activate the anti-tumor T cell response (31). Similar results have been obtained in a mouse model of melanoma (19), where Nam administered alone as a therapeutic agent reduced tumor growth and prolonged the survival of mice. Higher levels of IFN-g-producing cells were found in the peripheral blood of mice treated with Nam than in untreated mice.…”
Section: The Direct Role Of Nad +supporting
confidence: 74%
“…In addition, different cytokines/chemokines were modulated in Nam-treated mice (but not in untreated mice), including an increase of IL-5 and Eotaxin and a decrease of IL-10, IL-12, IL-3 and RANTES. Thus, Nam treatment is able to increase IFN-g secretion, which is pivotal for the anti-tumor immune response, and to modulate the balance of cytokine/ chemokine in the periphery (19). These studies confirmed the role of NAD + in the activation of anti-tumor T cell response and clarified one of the mechanisms underlying T cell inactivation after NAD + depletion, centered on metabolic reprogramming.…”
Section: The Direct Role Of Nad +mentioning
confidence: 52%
See 1 more Smart Citation
“…In conclusion, our study [ 9 ], and others [ 50 , 51 ], suggest that SIRT2 is a tumor promoter in melanoma cells and this sirtuin is a promising target in antimelanoma therapy; these levels may influence the overall survival of melanoma patients [ 51 ]. The present study shows that inhibition of SIRT2 (shRNA-mediated knockdown and pharmacological by thiomyristoyl) resulted in sensitization of melanoma cells to the widely used anticancer drug cisplatin, most likely by targeting EGFR stability and downstream signaling.…”
Section: Discussionmentioning
confidence: 77%
“…Otherwise, about a quarter of participants confirmed they are aware of scientific studies reporting a reduction of melanoma due to systemic photoprotection, mainly vitamin D, and that this supplement was even indicated in guidelines for melanoma. A very recent study reported that nicotinamide shows a relevant antimelanoma activity in vitro and in vivo in mice, demonstrating that this molecule significantly delayed tumor growth in vivo and improved survival of melanoma-bearing mice [ 22 ]. However, no studies demonstrated that oral photoprotection has a role in melanoma prevention in humans, and no oral photoprotector is indicated in guidelines for melanoma.…”
Section: Discussionmentioning
confidence: 99%